Anger Manajemen dalam Keningkatkan Mutu Kinerja Karyawan di Ma’had Aly Nurul Jadid - Ansori Ansori; Pahrul Iman; Fita Putridiyanti (Universitas Nurul Jadid, 2021)
Abstract: This study aims to analyze the Anger Management applied by leaders to all academics in Ma'had Aly Nurul Jadid, where its application has its own role for a leader, especially in develops the quality of employee performance, so that it has the ability to stabilize and improve employee performance in bearing their respective burdens. Anger management as an iron for a leader in stepping up and doing something to avoid mistakes that cause something negative. This research uses a qualitative approach of this type of case study, with a research site at ma'had aly Pondok Pesantren Nurul Jadid, Paiton, Probolinggo. The results of this study show that anger management in improving the quality of employee performance in ma'had aly has its own form. Anger management is tapped by the leader ma'had aly nurul jadid in improving the quality of employee performance through first self-control emotions, so that with the control can think about the impact that will occur. Both drivers of discipline, because by managing anger the leader will be able to control feelings and clear minds so that the things conveyed to employees will have an effect. Third as a nuance of Sufism in collaboration with the work of imam al-ghozali in his book Ihyak Ulumuddin. Fourth as a policy brake, so that in setting policy is not in a state of anger.